Normative values of the Epworth Sleepiness Scale (ESS), derived from a large German sample. - Sander, C.; Hegerl, U.; Wirkner, K.; Walter, N.; Kocalevent, R. D.; Petrowski, K.; Glaesmer, H.; Hinz, A. (Sleep Breath, 2016)
PURPOSE: Daytime sleepiness is associated with several medical problems. The aim of this paper is to provide normative values for one of the most often used questionnaires measuring daytime sleepiness, the Epworth Sleepiness Scale (ESS). METHODS: A large sample of 9711 people from the German general population took part in this study. In addition to the ESS, several other questionnaires were used, and sociodemographic and behavioral factors were recorded. RESULTS: Normative values for the ESS are given. According to the generally accepted criterion ESS > 10, 23 % of the sample showed excessive daytime sleepiness. Males reported significantly more daytime sleepiness than females (effect size d = 0.19). In the age range of 40-80 years, a continuous decline of daytime sleepiness was observed. Psychometric properties of the ESS were good. Alcohol intake and nicotine consumption were marginally associated with daytime sleepiness, and obese people reported significantly more sleepiness than people of normal weight (OR = 1.39). CONCLUSIONS: The normative tables allow clinicians and researchers to assess the degree of their patients' daytime sleepiness, especially in the upper range of scores.
Keywords: Adult; Aged; Aged, 80 and over; Alcohol Drinking/epidemiology; Disorders of Excessive Somnolence/*diagnosis/*epidemiology; Female; Germany; Humans; Male; Middle Aged; *Observer Variation; Psychometrics/*statistics & numerical data; Reference Values; Reproducibility of Results; Risk Factors; Sex Factors; Sleep Apnea, Obstructive/*diagnosis/*epidemiology; Smoking/epidemiology; Statistics as Topic; *Surveys and Questionnaires; Tobacco Use Disorder/epidemiology